Frequency of stepping down antibiotics and nebuliser treatment is lower at weekends compared to weekdays: an observational study - Lewis, Sarah; Langley, Tessa; Lacey, Julia; Skelly, Rob; Norwood, Mark; Sturrock, Nigel; Fogarty, Andrew W. (Royal College of Physicians, 2017)
We hypothesised that delays in providing non-urgent medication step-downs at weekends to medical management may be associated with increased length of stay.In a novel use of electronic prescribing data, we analysed emergency admissions from a busy acute medical hospital over 52 weeks from November 2014 to October 2015. The main outcomes of interest were switching from intravenous antibiotics to oral antibiotics and stopping nebulised bronchodilators. The rate of switching from intravenous to oral antibiotics was lower on Saturdays and Sundays compared with weekdays, and the rate of stopping nebulised bronchodilators was similarly lower at weekends (p<0.001). Median length of stay was shorter in those whose antibiotic treatment was stepped down at weekends compared with weekdays (4 days versus 5 days, p<0.001). Reduced medication step-downs at weekends may represent a bottleneck in patient flow. Electronic prescribing data are a valuable resource for future health services research.